Simulation of the urban mobile communication channel - Tao, Wang. (2009)
Urban and suburban communication channels are multipath fading channels. A number of problems such as signal fading, abrupt phase changes and path delay are caused by the multipath phenomenon. All of them can affect the quality of mobile communications. The development of new generation digital mobile communication systems calls for greater understanding of mobile RF propagation channels. Because it is expensive to do real tests, and hardware simulation is less flexible, both designers and service providers are interested in obtaining good computer simulation tools for RF propagation.